Pengaruh Iradiasi Gamma dan Asam Akrilat terhadap Sifat Mekanik Polimer Super Water Absorbent (SWA) Berbasis Onggok - Puspita, Indah; Kurniati, Mersi; Winarti, Christina (Jurnal Riset Fisika Indonesia, 2023)
The Super Water Absorbent (SWA) polymer is a type of polymer that has exceptional water absorption capabilities while remaining insoluble in water. In this study, the authors conducted research on the modification of SWA by including acrylic acid and acrylamide monomers, followed by a crosslinking process utilising gamma irradiation. This study investigated the impact of acrylic acid and gamma irradiation on the mechanical characteristics of SWA. The experimental findings demonstrated a notable enhancement in the mechanical properties of the hydrogel by the incorporation of acrylic acid. This was evidenced by a substantial rise in the hardness value, which rose from 11.09 mJ to 36.13 mJ.